2004
DOI: 10.1111/j.1467-8624.2004.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity With School English in African American Children and Its Relation to Early Reading Achievement

Abstract: For children whose everyday speech differs greatly from the School English (SE) they encounter in academic materials and settings, it was hypothesized that greater familiarity with SE would be associated with more successful early reading acquisition. Sentence imitation and reading skills of 217 urban African American students in kindergarten through second grade (ages 5 to 8 years) were assessed. Children in each grade varied widely in the extent to which their imitations of SE sentences included phonological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 27 publications
13
149
2
1
Order By: Relevance
“…Two separate studies (Craig, Thompson, Washington, & Potter, 2004;Craig, Zhang, Hensel, & Quinn, 2009) used a subsample of a larger study , but investigated different outcomes, and these three were combined to form one study. Another three studies provided outcomes disaggregated by grade level (Charity, Scarborough, & Griffin, 2004, Grades K-2; Kohler et al, 2007, Grades 1 and 3; Terry, 2006, Grades 1-3), resulting in a total of 20 observed study effect sizes. From these studies, 75 outcome effect sizes were coded: 59 for reading and 16 for writing and spelling; a simple mean was computed for the study's overall effect size.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Two separate studies (Craig, Thompson, Washington, & Potter, 2004;Craig, Zhang, Hensel, & Quinn, 2009) used a subsample of a larger study , but investigated different outcomes, and these three were combined to form one study. Another three studies provided outcomes disaggregated by grade level (Charity, Scarborough, & Griffin, 2004, Grades K-2; Kohler et al, 2007, Grades 1 and 3; Terry, 2006, Grades 1-3), resulting in a total of 20 observed study effect sizes. From these studies, 75 outcome effect sizes were coded: 59 for reading and 16 for writing and spelling; a simple mean was computed for the study's overall effect size.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…AAE and SAE are not distinguished by the absence or presence of specific features, but rather by the frequency and contexts in which these forms occur. Further, African American children vary in the density of AAE features produced in their speech, which is associated with gender and socioeconomic status (Charity, Scarborough, & Griffin, 2004;Washington, Craig, & Kushmaul, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The awareness of and representation of speech sounds with graphemes, awareness and representation of morpho-syntactic structures in spelling, and awareness and use of standard word and sentence forms each depend on the development of specific linguistic awarenesses (Bryant, Nunes, & Bindman, 2000) as well as, perhaps, a non-specific level of metalinguistic awareness that supports such skills as intrinsic and automatic comparison of dialects (Charity et al, 2004). As a tool to develop linguistic awareness, many applied linguists recommend that teachers teach students to contrast formal and informal grammatical patterns as part of writing instruction (e.g., Wheeler & Sword, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Recently it has also been demonstrated that young children who speak African American Vernacular English (AAVE) and who are less familiar with the forms of standard school English, as measured by a sentence repetition task, have more difficulty acquiring beginning reading skills (Charity, Scarborough, & Griffin, 2004) than classmates who can demonstrate greater familiarity with standard academic English. Dialect characteristics measured by the sentence repetition task included: consonant substitutions for /th/; omission or reduction of a consonant cluster; omission of a single consonant; omission or substitution of forms of the verb ''to be'', omission of verb tense inflection; omission of reflexive pronoun or change of pronoun; substitution of none or no for any; and substitution of a for an.…”
Section: Comprehension and Production Of Written Languagementioning
confidence: 98%